Cartographical Imaginations: Spatiality, Adult Education and Lifelong Learning - Richard Edwards; Ron Cervero; Julia Clarke; Brenda Morgan-Klein (Adult Education Research Conference, 2002)
This symposium explores the significance of space and spatiality for research in adult education and lifelong learning. Drawing on recent theorising in the social sciences, we examine empirically and theoretically questions of space, place and power in adult education.